2009
DOI: 10.1677/jme-08-0174
|View full text |Cite
|
Sign up to set email alerts
|

Molecular mechanisms by which hormones and cytokines regulate cell junction dynamics in the testis

Abstract: Hormones and cytokines are known to regulate cellular functions in all tissues including testis. These two groups of biomolecules exert a broad spectrum of effects on various aspects of spermatogenesis. Among them, one of the regulatory effects on spermatogenesis is to modulate cell junction restructuring between Sertoli cells and between Sertoli and germ cells in the seminiferous epithelium. The restructuring of cell junctions is crucial to enable the migration of germ cells along the seminiferous epithelium … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
22
0
1

Year Published

2010
2010
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 21 publications
(23 citation statements)
references
References 70 publications
0
22
0
1
Order By: Relevance
“…This was further emphasized by the results of our western blot analysis, which clearly indicated the presence of 12 kDa INSL3 in both interstitial and seminiferous compartments. These findings suggest that INSL3 enters the seminiferous compartment across the blood-testis barrier (BTB), which is created by inter-Sertoli tight junctions and adherens junctions (Lui & Lee 2009 be attributable to the opening of the BTB and take place concomitantly when physiological disassembly of tight junctions occurs to allow the passage of preleptotene spermatocytes across the BTB. This is based on the findings that the BTB separates mitotic spermatogonia from meiotic germ cells and is periodically disassembled to allow the passage of preleptotene spermatocytes across the barrier (Lui & Lee 2009, Mruk & Cheng 2010, Cheng & Mruk 2012.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This was further emphasized by the results of our western blot analysis, which clearly indicated the presence of 12 kDa INSL3 in both interstitial and seminiferous compartments. These findings suggest that INSL3 enters the seminiferous compartment across the blood-testis barrier (BTB), which is created by inter-Sertoli tight junctions and adherens junctions (Lui & Lee 2009 be attributable to the opening of the BTB and take place concomitantly when physiological disassembly of tight junctions occurs to allow the passage of preleptotene spermatocytes across the BTB. This is based on the findings that the BTB separates mitotic spermatogonia from meiotic germ cells and is periodically disassembled to allow the passage of preleptotene spermatocytes across the barrier (Lui & Lee 2009, Mruk & Cheng 2010, Cheng & Mruk 2012.…”
Section: Discussionmentioning
confidence: 99%
“…These findings suggest that INSL3 enters the seminiferous compartment across the blood-testis barrier (BTB), which is created by inter-Sertoli tight junctions and adherens junctions (Lui & Lee 2009 be attributable to the opening of the BTB and take place concomitantly when physiological disassembly of tight junctions occurs to allow the passage of preleptotene spermatocytes across the BTB. This is based on the findings that the BTB separates mitotic spermatogonia from meiotic germ cells and is periodically disassembled to allow the passage of preleptotene spermatocytes across the barrier (Lui & Lee 2009, Mruk & Cheng 2010, Cheng & Mruk 2012. Although no studies to date have identified the possible sites of action of INSL3 in the boar testis, RXFP2 mRNA and/or protein have been shown to be expressed in Leydig cells, germ cells, and/or Sertoli cells in different species, including humans (Anand- Ivell et al 2006a), rats (Kawamura et al 2004, Anand-Ivell et al 2006a), mice (Anand-Ivell et al 2006a, Feng et al 2007, roe deer (Hombach-Klonisch et al 2004), and goats .…”
Section: Discussionmentioning
confidence: 99%
“…Cytokine-mediated down-regulation of junction proteins results in an increase in BTB permeability [12]. Several studies have shown that transforming growth factor-b 3 (TGFB) and tumor necrosis factor a (TNF) are involved in regulating the transcription of claudin11, occludin, and zonula occluden 1 (ZO1), which are major components of tight junctions [13,14].…”
Section: Introductionmentioning
confidence: 99%
“…tiation until maturation through the spermatogenesis (Lui and Lee, 2009). To observe the effect of WSF on Leydig cells, testosterone in serum was measured by ELISA.…”
Section: Resultsmentioning
confidence: 99%